Suramin, an antiparasitic drug, stimulates adipocyte differentiation and promotes adipogenesis - Hanxiao Li; Yingyue Dong; Chunmiao Han; Lisha Xia; Yue Zhang; Tongsheng Chen; Huamin Wang; Guoheng Xu (Lipids in Health and Disease, 2023)
Abstract Background Previous studies demonstrated that mast cells with their degranulated component heparin are the major endogenous factors that stimulate preadipocyte differentiation and promote fascial adipogenesis, and this effect is related to the structure of heparin. Regarding the structural and physiological properties of the negatively charged polymers, hexasulfonated suramin, a centuries-old medicine that is still used for treating African trypanosomiasis and onchocerciasis, is assumed to be a heparin-related analog or heparinoid. This investigation aims to elucidate the influence of suramin on the adipogenesis. Methods To assess the influence exerted by suramin on adipogenic differentiation of primary white adipocytes in rats, this exploration was conducted both in vitro and in vivo. Moreover, it was attempted to explore the role played by the sulfonic acid groups present in suramin in mediating this adipogenic process. Results Suramin demonstrated a dose- and time-dependent propensity to stimulate the adipogenic differentiation of rat preadipocytes isolated from the superficial fascia tissue and from adult adipose tissue. This stimulation was concomitant with a notable upregulation in expression levels of pivotal adipogenic factors as the adipocyte differentiation process unfolded. Intraperitoneal injection of suramin into rats slightly increased adipogenesis in the superficial fascia and in the epididymal and inguinal fat depots. PPADS, NF023, and NF449 are suramin analogs respectively containing 2, 6, and 8 sulfonic acid groups, among which the last two moderately promoted lipid droplet formation and adipocyte differentiation. The number and position of sulfonate groups may be related to the adipogenic effect of suramin. Conclusions Suramin emerges as a noteworthy pharmaceutical agent with the unique capability to significantly induce adipocyte differentiation, thereby fostering adipogenesis.